Interaction of renal failure and dyslipidaemia in the development of calcific aortic valve disease in rats. Issue 5 (3rd September 2017) - Gillis, Kris; Roosens, Bram; Bala, Gezim; Remory, Isabel; Hernot, Sophie; Delvenne, Philippe; Mestrez, Fabienne; Droogmans, Steven; Cosyns, Bernard
Abstract: Objective: Calcific aortic valve disease (CAVD) is currently the most common heart valve disease worldwide and is known to be an active process. Both renal failure and dyslipidaemia are considered to be promoting factors for the development of valvular calcifications. The aim of this study is to prospectively evaluate the respective contribution and interaction of renal failure and dyslipidaemia on CAVD in a rat model, using echocardiography and compared with histology. Methods and results: Sixty-eight male Wistar rats were prospectively divided in eight groups, each fed a different diet to induce renal failure alone and combined with hyperlipidaemia or hypercholesterolemia. CAVD was detected and quantified by calibrated integrated backscatter of ultrasound (cIB) and compared with the histological calcium score. The study follow-up was 20 weeks. At the end of the study, the cIB value and the calcium score of the aortic valve were significantly increased in the group with isolated renal failure but not with dyslipidaemia. The combination of renal failure with high cholesterol or high-fat diet did not significantly increase calcifications further. Conclusions: Renal failure alone does induce aortic valve calcifications in a rat model of CAVD, whereas dyslipidaemia alone does not. The combination of renal failure with dyslipidaemia does not increase calcification further. These findings suggest that a combination of atherosclerotic and calcifying factors is not required to induce aortic valve calcifications in this model.